Inventario del tarwi (lupinus mutabilis), yacón (smallanthus sonchifolius), poroto (phaseolus vulgaris) y poro-poro (passiflora tripartita), especies vegetales nativas de La Libertad con potencial de industrialización - Monzón Acosta, Reynaldo Joel (2015)
The aim of this study was to make an inventory of the “tarwi” (Lupinus mutabilis), “yacón” (Smallanthus sonchifolius), “poroto” (Phaseolus vulgaris) and “poro-poro” (Passiflora tripartita), native plants with potential freedom of industrialization. The inventory for a taxonomic classification was performed for each species using the proposed system by Engler (1964). It has also been made a literature review of each species detailing the characteristics of each one, the towns of the region with the greatest wealth of native flora was identified and a trip of a scientific nature was conducted whose aim was to inventory the native plants (“yacon”, “tarwi”, “poro poro” and “poroto”), carrying out the following procedure: Delimitation and description of the land, gathering samples, pictures, interviews to the residents and studious people of the area. As result of this process, the districts of Huamachuco, Chugay, Sarin and Sanagorán were visited in the province of Sanchez Carrion, to determine the production of “yacón”, “poroto”, “poro poro“ and “tarwi” respectively. It was determined that production is growing more for the ”tarwi” with 3539.50 hectares, followed by “yacón” with 13.29 hectares, the “poro poro” with 7 hectares and the “poroto” which does not report production data. It was also determined that the end-use production in all cases is for local market consumption. This paper confirms the lack of use of these native species at the industrial level, despite having great potential in the industry.